Bacteriological profile and antibiotic susceptibility patterns of bloodstream infection at Tripoli University Hospital (Journal of Medical Sciences, 2023)
Bloodstream infections remain one of the most significant causes of morbidity and death in healthcare settings throughout the world and are frequent reasons for getting medical care in the community, particularly in developing countries. This study is aimed at identifying a bacteriological profile and an antibiotic susceptibility pattern in blood cultures isolated from patients attending Tripoli University Hospital (TUH). This retrospective cross-sectional study has been carried out in a microbiology lab on blood cultures of patients suspected of having bloodstream infections from different wards in the Tripoli University Hospital over a period from May to November 2022. Blood samples were examined, isolated bacteria were identified using standard techniques, and then antimicrobial sensitivity testing was performed using CLSI guidelines. Out of 730 blood samples, 24.8% were culture-positive. Out of the 24.8% positive cultures, 15.1% were Gram-positive and 9.7% were Gram-negative. The most predominant organism was Staphylococcus epidermidis (7.1%), followed by Klebsiella species (5.6%). Most of the Gram-positive bacteria were susceptible to Linezolid, Clindamycin, Tetracycline, and Erythromycin. Most of the Gram-negative bacteria showed sensitivity to Imipenem, followed by Amikacin, Levofloxacin, and Trimethoprim/sulfamethoxazole. In conclusion, the present study shows an important prevalence of bacterial isolates in the blood and emphasizes the requirement for continuous monitoring of the susceptibility of the bacterial pathogens to antibiotics to avoid unsuitable use of the antibiotics.